Evidence of Native Cs Impurities and Metal–Insulator Transition in MoS2 Natural Crystals. (13th April 2016) - Molle, Alessandro; Fabbri, Filippo; Campi, Davide; Lamperti, Alessio; Rotunno, Enzo; Cinquanta, Eugenio; Lazzarini, Laura; Kaplan, Daniel; Swaminathan, Venkataraman; Bernasconi, Marco; Longo, Massimo; Salviati, Giancarlo
Abstract : In the realm of layered materials beyond graphene, MoS2 gains a primary role due to its semiconducting nature and n ‐type transport down to the 2D limit that makes it extremely appealing for electronic and optoelectronic applications. The intrinsic presence of defects causes MoS2 to undergo localization effects. In the present work, solid evidence of Cs impurities in bulky MoS2 crystals in a concentration well beyond the sensitivity threshold of independent compositional spectrometry probes is brought. Unlike conventional intercalation of alkali metals in MoS2, on the basis of the measured crystal structure and ab initio calculations, it is proposed that the incorporation of Cs is stabilized by complex where one Cs atom is associated with a double S vacancy therein resulting in an overall n ‐type doping of the MoS2 . The field effect transistor based on this kind of Cs‐doped MoS2 multilayer flakes exhibits a variable range hopping transport and a metal–insulator transition. Abstract : Evidence of Cs impurities in multilayer MoS2 crystals is described as Cs incorporation inside S divacancy complexes thereby inducing an overall n ‐type doping. A variable range hopping transport and a metal‐insulator transition are observed in the same MoS2 crystals, which are related to the excess charge and structural disorder possibly imparted by native impurities such as Cs.